Unlocking the Potential of Meldonium: From Performance Enhancement to Therapeutic Insights - Val Bellman (Psychoactives, 2024)
Meldonium, a promising pharmacological agent initially developed for cardiovascular indications, has sparked considerable interest in recent years due to its potential performance-enhancing effects. This review manuscript delves into the multifaceted roles of meldonium, examining its pharmacological mechanisms, therapeutic applications, and controversial implications in medicine. Beyond its cardiovascular applications, emerging research has shed light on meldonium’s neuroprotective properties and its potential for mitigating various psychiatric conditions. Moreover, recent investigations have explored meldonium’s potential in treating neurodegenerative disorders, alcohol use disorder, and even enhancing cognitive function. However, meldonium’s journey extends beyond the realm of medicine, as its use among athletes has stirred debates surrounding performance enhancement and fair competition. The substance’s inclusion in the World Anti-Doping Agency’s (WADA) prohibited list has intensified scrutiny and raised ethical considerations regarding its use in sports. This manuscript aims to provide a comprehensive resource for researchers, clinicians, and enthusiasts alike, fostering a deeper understanding of meldonium’s complex biological interactions and its potential contributions to psychiatry.